Shining a light on the road towards conducting principle-based co-production research in rehabilitation - Bourke, John A.; Bragge, Peter; River, Jo; Sinnott Jerram, K. Anne; Arora, Mohit; Middleton, James W. (Frontiers in Rehabilitation Sciences, 2024)
Moving from participatory approaches incorporating co-design to co-production in health research involves a commitment to full engagement and partnership with people with lived experience through all stages of the research process -start to finish. However, despite the increased enthusiasm and proliferation of research that involves co-production, practice remains challenging, due in part to the lack of consensus on what constitutes co-production, a lack of guidance about the practical steps of applying this approach in respect to diverse research methods from multiple paradigms, and structural barriers within academia research landscape. To navigate the challenges in conducting coproduced research, it has been recommended that attention be paid to focusing and operationalising the underpinning principles and aspirations of co-production research, to aid translation into practice. In this article, we describe some fundamental principles essential to conducting co-production research (sharing power, relational resilience, and adopting a learning mindset) and provide tangible, practical strategies, and processes to engage these values. In doing so, we hope to support rehabilitation researchers who wish to engage in co-production to foster a more equitable, ethical, and impactful collaboration with people with lived experience and those involved in their circle of care.